Mutual funds' appetite for sustainability in European Auto ABS - Carmelo Latino; Loriana Pelizzon; Max Riedel; Yue Wang (Leibniz Institute for Financial Research SAFE, 2025)
Using hand-collected data on European auto asset-backed securities (Auto ABS), we examine the role of mutual funds in financing the transition to zero-emission mobility. Mutual funds, particularly those with a green mandate, tend to have a higher exposure to sustainability-transparent Auto ABS and tend to allocate more capital to deals with a higher proportion of electric vehicles. However, we find no clear preference for portfolios with lower average CO2 emissions. This behaviour suggests that, in the absence of a globally recognized framework for green securitizations, asset managers rely on sustainability proxies that are associated with the lowest disclosure processing costs. Our analysis provides important new evidence on how standardized sustainability disclosures at both the prospectus and loan levels could influence asset allocation.
Keywords: G11; G18; G20; Q56; 330; Auto ABS; Car Loans; Zero- or low-emission vehicles; Mutual funds; Securitization; Sustainable Finance